TESTING OF HYBRID NICKEL-POLYURETHANE FOAMS AT HIGH STRAIN-RATES USING HOPKINSON BAR AND DIGITAL IMAGE CORRELATION - Marcel Adorna; Petr Zlámal; Tomáš Fíla; Jan Falta; Markus Felten; Michael Fries; Anne Jung (Acta Polytechnica CTU Proceedings, 2018)
In this paper Split Hopkinson pressure bar (SHPB) was used for dynamic testing of nickel coated polyurethane hybrid foams. The foams were manufactured by electrodeposition of a nickel coating on the standard open-cell polyurethane foam. High strength aluminium alloy bars instrumented with foil strain-gauges were used for dynamic loading of the specimens. Experiments were observed using a high-speed camera with frame-rate set to approx. 100-150 kfps. Precise synchronisation of the high-speed camera and the strain-gauge record was achieved using a through-beam photoelectric sensor. Dynamic equilibrium in the specimen was achieved in all measurements. Digital image correlation technique (DIC) was used to evaluate in-plane displacements and deformations of the samples. Specimens of two different dimensions were tested to investigate the collapse of the foam structure under high-speed loading at the specific strain-rate and strain.